Efficacy of Conservative and Surgical Techniques in the Management of Scaphoid Fractures: A Longitudinal Study - Hamza Fareed, Niaz Hussain Keerio, Ahmed Elkhashab, Bader Mohammed H Alqarni, Sher Baz Khan, Waseem Ahmed (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The goal of this study was to assess the efficacy of conservative versus surgical treatment for acute scaphoid fracture. Study design: A longitudinal study Place and Duration: This study was conducted at Fauji Foundation Hospital, Rawalpindi, MMC college Mirpurkhas, BMCH Quetta, PHQ hospital Gilgit Pakistan from June 2020 to June 2021. Methodology: A total of 60 acute scaphoid fractures (within three weeks) were included in this study, regardless of location. During the clinical examinations, diagnostic tests were done. Patients were urged to have wrist radiography check if any of these tests were positive. If radiography revealed no fracture, the wrist was immobilised with a below-elbow slab, and the patient was instructed to return in 15 days. After two weeks, the identical x-ray series was repeated Results: During the study period, 60 cases of acute scaphoid fracture (< 3 weeks) were seen. The average age of patients was 36.5 years. There were n=48 (80%) male patients and n=12 (20%) female patients. A right-side fracture was found in 38 (63 %) of patients, while a left-side fracture was found in 22 (36 %). The most common type of injury was traffic accidents, but sports injuries, industrial injuries, domestic injuries, and assault injuries were also common. A total of 11 patients had poor results who were managed conservatively. Poor results were reported in 1 patient of the operatively managed patients. Conclusion: As compared to conservative management, surgical technique had more favourable outcome. There were poor results in every fourth patient that was managed conservatively, while poor results were negligible in patients who were operatively managed.